THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP AND WORKPLACE SPIRITUALITY ON TEACHER PERFORMANCE WITH WORK MOTIVATION AS A MEDIATOR AT XYZ ELEMENTARY SCHOOL IN KUPANG CITY [PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN SPIRITUALITAS KERJA TERHADAP KINERJA GURU DENGAN MOTIVASI KERJA SEBAGAI MEDIATOR DI SEKOLAH DASAR DI KOTA KUPANG] - Pian, Rutsri Marlinda; Tung, Khoe Yao (Universitas Pelita Harapan, 2025)
This research is a quantitative study aimed at examining the influence of transformational leadership and workplace spirituality on teacher performance with work motivation as a mediator at XYZ Elementary School in Kupang City. This study involved 35 teachers working at the school, with data collected through an online questionnaire that had been tested for validity and reliability. Data analysis was conducted using the statistical method Partial Least Square-Structural Equation Modeling (PLS-SEM), including path analysis and mediation effect testing. The results of the study indicate that 1) there is no positive and significant influence of transformational leadership on teacher performance, 2) there is no positive and significant influence of transformational leadership on work motivation, 3) there is a positive and significant influence of workplace spirituality on teacher performance, 4) there is a positive and significant influence of workplace spirituality on work motivation, 5) there is a positive and significant influence of work motivation on teacher performance, 6) there is no positive and significant influence of transformational leadership on teacher performance mediated by work motivation, and 7) there is no positive and significant influence of workplace spirituality on teacher performance mediated by work motivation. Abstrak bahasa Indonesia Penelitian ini merupakan penelitian kuantitatif yang bertujuan mengkaji pengaruh kepemimpinan transformasional dan workplace spirituality terhadap kinerja guru dengan motivasi kerja sebagai mediator di SD XYZ Kota Kupang. Penelitian ini melibatkan 35 guru yang bekerja di sekolah tersebut, dengan data dikumpulkan melalui kuesioner yang dibagikan secara online dan telah diuji validitas dan reliabilitasnya. Analisis data dilakukan menggunakan metode statistik Partial Least Square-Structural Equation Modeling (PLS-SEM), yaitu analisis jalur dan uji efek mediasi. Hasil penelitian menunjukkan bahwa 1) tidak terdapat pengaruh positif dan signifikan kepemimpinan transformasional terhadap kinerja guru, 2) tidak terdapat pengaruh positif dan signifikan kepemimpinan transformasional terhadap motivasi kerja, 3) terdapat pengaruh positif dan signifikan workplace spirituality terhadap kinerja guru, 4) terdapat pengaruh positif dan signifikan workplace spirituality terhadap motivasi kerja, 5) terdapat pengaruh positif dan signifikan motivasi kerja terhadap kinerja guru, 6) tidak terdapat pengaruh positif dan signifikan kepemimpinan transformasional terhadap kinerja guru yang dimediasi oleh motivasi kerja, dan 7) tidak terdapat pengaruh positif dan signifikan workplace spirituality terhadap kinerja guru yang dimediasi oleh motivasi kerja.